2013
DOI: 10.1007/s13197-013-1068-x
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent procedure for watermelon ripeness detection based on vibration signals

Abstract: In this paper, an efficient procedure for ripeness detection of watermelon was presented. A nondestructive method was used based on vibration response to determine the internal quality of watermelon. The responses of samples to vibration excitation were optically recorded by a Laser Doppler (LD) vibrometer. Vibration data was collected from watermelons of two qualities, namely, ripe and unripe. Vibration signals were transformed from time-domain to frequency-domain by fast Fourier transform (FFT). Twenty nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…Such data are useful for the nondestructive determination of fruit firmness and maturity (Abbaszadeh et al, 2015;Oveisi et al, 2014;. In this study, we further demonstrated through actual measurements that the f 3 /f 2 ratio is a powerful tool for the nondestructive detection of split pit in peaches.…”
Section: Future Use Of the Acoustic Vibration Methods For Commercial Pmentioning
confidence: 61%
See 1 more Smart Citation
“…Such data are useful for the nondestructive determination of fruit firmness and maturity (Abbaszadeh et al, 2015;Oveisi et al, 2014;. In this study, we further demonstrated through actual measurements that the f 3 /f 2 ratio is a powerful tool for the nondestructive detection of split pit in peaches.…”
Section: Future Use Of the Acoustic Vibration Methods For Commercial Pmentioning
confidence: 61%
“…This method has been developed to estimate fruit firmness . The f 2 frequency has also been used to evaluate flesh firmness and/or optimal ripeness of fruit, including melons (Taniwaki et al, 2009c, pears Oveisi et al, 2014;Taniwaki et al, 2009b;Terasaki et al, 2006), persimmons (Taniwaki et al, 2009a), kiwifruits (Terasaki et al, 2013), watermelons (Abbaszadeh et al, 2015), and grapes (Takahashi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic vibration method was initially developed to estimate fruit firmness , but has seen increasing use in the evaluation of the maturity of various agricultural products, including persimmons (Taniwaki et al, 2009a), pears Oveisi et al, 2014;Taniwaki et al, 2009b;Terasaki et al, 2006), grapes (Takahashi et al, 2010), kiwifruit (Terasaki et al, 2013), melons (Taniwaki et al, 2009c, and watermelons (Abbaszadeh et al, 2015;Ali et al, 2017). In addition to fruit firmness, Kadowaki et al (2012) adopted this method to detect the inner, local deterioration of Japanese pear fruit infected by core rot.…”
Section: Introductionmentioning
confidence: 99%
“…[33] Laser Doppler Vibrometry (LDV) is one of the methods that has been investigated in determining ripeness of fruits. As in Figure 14, a watermelon fruit is placed on a shaker which is then vibrated according to random wave signal frequencies where the vibration spectrum response of the watermelon will be recorded by LDV [37]. Based on different spectrum patterns, the ripeness of the watermelon is then identified.…”
mentioning
confidence: 99%